the effect of training in the playground sand on the explosive power of Soccer players (U19 years) - azzali.khalifa; taoutaou zohra (sports creativity, 2025)
The aim of this study is to compare the effect of training in the playground (sand - artificial grass) on the explosive power of Soccer players (U19 years). The hypothesize were a statistically significant differences in the exploding power in both of the research groups and for the experimental group (sand) in the post-test, after identifying the original research community, the experimental method was selected to suit the aims of this study, the sample was (16 players) was selected randomize, they divided into two groups control and experimental group (8 players) for each group, training exercises were applied for 8 weeks with 2 times per week. A Sargent vertical jump test used to measure the explosive power, the SPSS package used to analyze the results, Through presenting and analyzing the results, we found that the rate of improvement in explosive power was greater in the experimental group, this indicates the effectiveness of training on the playground sand in the development of explosive force in the soccer players.